Isolation and Functional Characterization of an Acidic Myotoxic Phospholipase A₂ from Colombian Bothrops asper Venom - Posada Arias, Silvia; Rey-Suárez, Paola; Pereáñez J, Andrés; Acosta, Cristian; Rojas, Mauricio; Delazari Dos Santos, Lucilene; Ferreira, Rui Seabra; Núñez, Vitelbina (MDPI, 2017)
Myotoxic phospholipases A₂ (PLA₂) are responsible for many clinical manifestations in envenomation by Bothrops snakes. A new myotoxic acidic Asp49 PLA₂ (BaCol PLA₂) was isolated from Colombian Bothrops asper venom using reverse-phase high performance liquid chromatography (RP-HPLC). BaCol PLA₂ had a molecular mass of 14,180.69 Da (by mass spectrometry) and an isoelectric point of 4.4. The complete amino acid sequence was obtained by cDNA cloning (GenBank accession No. MF319968) and revealed a mature product of 124 amino acids with Asp at position 49. BaCol PLA₂ showed structural homology with other acidic PLA₂ isolated from Bothrops venoms, including a non-myotoxic PLA₂ from Costa Rican B. asper. In vitro studies showed cell membrane damage without exposure of phosphatidylserine, an early apoptosis hallmark. BaCol PLA₂ had high indirect hemolytic activity and moderate anticoagulant action. In mice, BaCol PLA₂ caused marked edema and myotoxicity, the latter seen as an increase in plasma creatine kinase and histological damage to gastrocnemius muscle fibers that included vacuolization and hyalinization necrosis of the sarcoplasm.
Keywords: acidic myotoxic phospholipase A2; Bothrops asper; edema; myotoxicity; snake venom